The Effect of Ion-Plasma Treatment on Micromechanical Characteristics of Compositional Layers in Austenitic Stainless Steel with Different Grain Sizes; AIP Conference Proceedings; Vol. 2167 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2019 (AMHS'19) - Moskvina V. Valentina (2019, 2019)
Title screen